Chitin - Mansencal, Rachel; Kadla, John F.; Braun, Jennifer L. (Polymer Data Handbook, 2009)
Natural Resources Chitin is a biopolymer found in crustaceans shells (crab, shrimp, prawn, lobster) in some mollusks (krill, oyster, clam shells, squid skeleton). It is also found in fungi (mushrooms, yeast) and in various insects (cockroaches, silkworms, spiders, beetles).